In Search of a Dramatic Equilibrium : Was the Armenian Dram Overvalued? - Oomes, Nienke; Minasyan, Gohar; Stepanyan, Ara.; Stepanyan, Vahram (Washington, D.C. : International Monetary Fund, 2009)
This papers estimates the equilibrium exchange rate for Armenia using three different approaches: the purchasing power parity (PPP) approach, the behavioral equilibrium exchange rate (BEER) approach, and the external sustainability (ES) approach. All three approaches suggest that the dram was overvalued by about 20-30 percent prior to the devaluation of the dram in March 2009.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet